The Role of Students’ Perception and Informatioin Technology in Improving The Production of (Θ) and (Ð) by 1thSemester Students of STIKOM Tunas Bangsa Pematangsiantar - Jalaluddin (The Explora, 2022)
The productions of the English consonants (θ) and (ð) are constant difficulties faced by English learners whose mother tongue is not English. The failure in perfect productions of these consonants very often goes on to the time when the students’ speech sound plays a key part in their career. With the role of students’ perception of correct positions of the articulators against the required points of articulation in producing the dental fricative consonant sounds (θ) and (ð) and information technology,,the students can improve the quality of the productions even to perfect state.